Analisis Kondisi Angin Menggunakan Diagram Windrose Sebagai Potensi Pembangkit Listrik Tenaga Bayu di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Sirait, Ratni; Lubis, Lailatul Husna; Noveni, Tasya (Proklamasi 45 University, 2023)
Indonesia's energy needs are increasing in line with population growth, economic growth, and people's energy consumption patterns. This causes the fossil energy sources in Indonesia to continue to run low. So alternative energy is needed in the form of new and renewable energy. An analysis of surface wind patterns has been carried out in Percut Sei Tuan District, Deli Serdang Regency. This study aims to determine the conditions of wind speed and direction in Percut Sei Tuan District, Deli Serdang Regency, as a basis for knowing the potential of wind energy in the region. Diagram analysis uses the windrose method using the WRPLOTS application. The wind condition data used is daily wind direction and speed data from January 1, 2013, through December 31, 2021, based on the online BMKG database. From the results of the analysis using the windrose method, it is found that the dominant wind direction blows from the north, which occurs in January, February, March, April, November, and December. The average wind speed ranges from 2.1 to 3.6 m/s, which is relatively low when used as an alternative energy source.